Wulff in a cage gold nanoparticles as contrast agents for computed tomography and photoacoustic imaging. Issue 39 (2nd October 2018) - Hajfathalian, Maryam; Amirshaghaghi, Ahmad; Naha, Pratap C.; Chhour, Peter; Hsu, Jessica C.; Douglas, Keely; Dong, Yuxi; Sehgal, Chandra M.; Tsourkas, Andrew; Neretina, Svetlana; Cormode, David P.
Abstract : A core–shell nanostructure yields balanced contrast production for both CT and photoacoustics. Abstract : Nanostructures have potential for use in biomedical applications such as sensing, imaging, therapeutics, and drug delivery. Among nanomaterials, gold nanostructures are of considerable interest for biomedical research, owing to their bio-inertness, controllable surface chemistry, X-ray opacity, and optical properties. Gold nanocages are particularly attractive for imaging and therapeutic applications, because they strongly absorb light in the near infra-red region which has high light transmission in tissue. However, the X-ray attenuation of nanocages is relatively low due to their hollow structure. In this study, for the first time, we sought to combine the attractive optical properties of nanoshells with the high payloads of solid nanoparticles and investigated their biomedical applications. Here, we report the engineering of Wulff in a cage nanoparticles via converting gold Wulff-shaped seeds into gold–silver core–shell structures and then performing a galvanic replacement reaction. The structure of these nanoparticles was determined using transition electron microscopy. This morphological transformation of gold nanoparticles shaped as truncated octahedrons into a complex Wulff in a cage nanoparticles during the reaction resulted in extensive changes in their optical properties that made these unique structures a potential contrast agent for photoacoustic imaging. We found that the Wulff in a cage nanoparticles had no adverse effects on the viabilities of J774A.1, Renca, and HepG2 cells at any of the concentrations tested. In vitro and in vivo experiments showed robust signals in both photoacoustic imaging and computed tomography. To the best of our knowledge, this is the first report of Wulff in a cage nanoparticles serving as a platform for multiple imaging modalities. This unique multifunctional nanostructure, which integrates the competencies of both core and shell structures, allows their use as contrast agents for photoacoustic imaging, computed tomography and as a potential agent for photothermal therapy.